Verity - Hoover, Colleen ([Place of publication not identified] : [publisher not identified], 2018)
"Lowen Ashleigh is a struggling writer on the brink of financial ruin when she accepts the job offer of a lifetime. Jeremy Crawford, husband of bestselling author Verity Crawford, has hired Lowen to complete the remaining books in a successful series his injured wife is unable to finish. Lowen arrives at the Crawford home, to sort through years of Veritys notes and outlines, hoping to find enough material to get started. Lowen uncovers an unfinished autobiography Verity never intended anyone to read, with pages of bone-chilling admissions, including Veritys recollection of the night their family was forever altered. Lowen decides to keep the manuscript hidden from Jeremy, knowing its contents would devastate him. But as Lowens feelings for Jeremy begin to intensify, she recognizes all the ways she could benefit, if he were to read his wifes words. After all, no matter how devoted Jeremy is to his injured wife, a truth this horrifying would make it impossible for him to continue to love her"- -
Keywords: Married people -- Fiction; Women authors -- Fiction; Secrecy -- Fiction; Family secrets -- Fiction; Man-woman relationships -- Fiction; Romantic suspense fiction; Romance fiction; Thrillers (Fiction)